2011
DOI: 10.1161/strokeaha.110.595926
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients With ≥70% Symptomatic Intracranial Stenosis After Wingspan Stenting

Abstract: Background and Purpose-There were limited data on the long-term outcome of patients with symptomatic intracranial atherosclerotic stenosis Ն70% after Wingspan stenting. Using our Wingspan cohort data and the data from the Warfarin and Aspirin for Symptomatic Intracranial Atherosclerotic Disease (WASID) as a historical control, we tested the hypothesis that stenting provided no benefit over antithrombotic therapy alone for these high-risk patients. Methods-Between January 2007 and February 2009, 100 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 13 publications
(14 reference statements)
3
74
1
Order By: Relevance
“…Our results are comparable with the recent data (1-month stroke and/or death rate of 4.4%-6.2%) derived from some high-volume centers (Ͼ100 cases per year). [17][18][19] A retrospective analysis of 96 patients treated with intracranial angioplasty and stent placement at 3 university-affiliated institutions in the United States reported that the overall 1-month stroke and/or death rate was 7.2% in the 69 SAMMPRIS-eligible group and 7.4% in the 27 SAMMPRIS-ineligible group. 20 The 30-day stroke and/or death rate was 3.3% and 10.2% in the SAMMPRIS-eligible, angioplasty-treated subgroup and the stent-treated subgroup, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are comparable with the recent data (1-month stroke and/or death rate of 4.4%-6.2%) derived from some high-volume centers (Ͼ100 cases per year). [17][18][19] A retrospective analysis of 96 patients treated with intracranial angioplasty and stent placement at 3 university-affiliated institutions in the United States reported that the overall 1-month stroke and/or death rate was 7.2% in the 69 SAMMPRIS-eligible group and 7.4% in the 27 SAMMPRIS-ineligible group. 20 The 30-day stroke and/or death rate was 3.3% and 10.2% in the SAMMPRIS-eligible, angioplasty-treated subgroup and the stent-treated subgroup, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the current study, the China Angioplasty and Stenting for Symptomatic Intracranial Severe Stenosis trial has been initiated and is an ongoing, prospective, multicenter randomized trial, which is being conducted in 8 sites intending to recruit 380 subjects (stent placement, 190; medical treatment alone, 190). 28 The study aims to demonstrate a 10.7% absolute reduction in ipsilateral stroke and/or death during 12 months (assuming an event rate of 18% for medically treated patients 3 and 7.3% for stenttreated patients 19 ). The sample size provides 80% power with a 2-sided test at the 5% level of significance and provides a 20% rate of lost follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although the self-expanding Wingspan stent system was not promising for patients with recent mild stroke (median time from qualifying events of 7 days) when compared with aggressive medical therapy in the Stenting and Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial, 46 clinical outcomes after the Wingspan were generally favorable in reports from China (including 100 patients; median, 29.5 days) 47 and Korea (77 patients; median, 15 days). 48 In Japan, the Wingspan was approved for commercial use in 2013 after a small domestic trial involving 20 patients with symptomatic intracranial stenosis.…”
Section: Strokementioning
confidence: 99%
“…Intracranial angioplasty and stenting has become an important approach in combination with intensive medications to treat intracranial stenosis (3,5). Compared with extracranial ICA stenting (9,10), stenting in the intracranial ICA segments is relatively immature with more perioperative complications, higher long-term in-stent restenosis rates, and higher recurrent rates of ischemic stroke (11,12).…”
Section: Discussionmentioning
confidence: 99%